Benefits of Motion in Animated Storybooks for Children’s Visual Attention and Story Comprehension. An Eye-Tracking Study - Takacs, Zsofia K.; Bus, Adriana G. (Frontiers in Psychology, 2016)
The present study provides experimental evidence regarding 4–6-year-old children’s visual processing of animated versus static illustrations in storybooks. Thirty nine participants listened to an animated and a static book, both three times, while eye movements were registered with an eye-tracker. Outcomes corroborate the hypothesis that specifically motion is what attracts children’s attention while looking at illustrations. It is proposed that animated illustrations that are well matched to the text of the story guide children to those parts of the illustration that are important for understanding the story. This may explain why animated books resulted in better comprehension than static books.